Factors Associated With Fear of Cancer Recurrence in Family Caregivers of Cancer Survivors: A Systematic Review - O'Rourke, Louise; Fisher, Peter L.; Campbell, Sophie; Wright, Amelia; Cherry, Mary Gemma (Frontiers in Psychology, 2021)
Objective: Fear of cancer recurrence (FCR) is a significant concern for family caregivers of cancer survivors and is associated with many adverse outcomes, including increased emotional distress and poorer quality of life. Although several theoretical models have been proposed to account for FCR in cancer survivors, their applicability to caregivers is unknown. The aim of this review was to identify clinical, demographic and psychological factors that are associated with, and predict, FCR in caregivers of cancer survivors. Method: AMED, CINAHL, Medline, PsycINFO, and Scopus were systematically searched for relevant studies reporting quantitative data on factors associated with FCR or similar constructs (e.g., worry or anxiety about cancer recurrence) in family caregivers of adult cancer survivors. Included studies were assessed for methodological quality using a standardized checklist adapted from the Agency for Healthcare Research and Quality. Results: Sixteen studies, half of which were cross-sectional, were included and summarized narratively. Non-modifiable factors, including age (n = 6) and treatment modality (n = 4), were found to be associated with increased FCR. Significant positive associations were also reported between illness perceptions and FCR (n = 3). However, there was heterogeneity across included studies with regards to factors examined and most were conducted in the USA. There were also several methodological limitations to the included studies. Conclusions: Research examining FCR in caregivers of cancer survivors has predominantly focused on demographic and clinical factors. Given the paucity of research exploring the psychological mechanisms underpinning FCR, future research should investigate theoretical underpinnings of FCR in caregivers of cancer survivors to support the development of psychological interventions for this population. Systematic Review Registration: PROSPERO, identifier [CRD42019119729].